EARLY WARNING OF RAINFALL-INDUCED LANDSLIDES AND DEBRIS FLOWS ON MT. BAWAKARAENG, SOUTH SULAWESI,INDONESIA - Hasnawir, Hasnawir (Secretariat of Forestry Research and Development Agency, 2013)
Rainfall thresholds that form the basis of the landslide warning systems now exist for a few areas in Indonesia. Based on analysis of historical data, threshold performance varies according to precipitation characteristics, and threshold exceed corresponds to a given probability of landslide occurrence. Early warnings of landslides and debris flows that include specific information about affected areas, probability of landslide and debris flow occurrence, and expected timing are technically feasible as illustrated by a case study made on Mt. Bawakaraeng, South Sulawesi, Indonesia. Records from 1997 to 2007 of rainfall data and history of landslides and debris flows were collected from the Ministry of Public Works of the government of Indonesia. The threshold, as defined by the lower boundary of the points representing landslides and debris-triggering rainfall events, is expressed by the equations I= 41.85D-0,85 before the large scale landslide on March 26, 2004 and I = 37.71D-0,90after the large scale landslide, where I is the rainfall intensity (mm/hr) and D is the duration of rainfall (hr). According to empirical threshold analysis, the regression curve can be considered as a reliable rainfall intensity- duration threshold for the study area, above which, landslide or debris flow event may occur.